Good corporate governance as moderating effect of tax avoidance and tax risk on company risk - Harianti, Tri; Hapsari, RR. Prima Dita (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
The phenomena of tax avoidance and stock price fluctuations in several mining and property companies remain a significant concern for businesses as they can give rise to various risks. Therefore, this research aims to examine and analyze the influence of tax avoidance and tax risk on corporate risk, considering good corporate govern-ance as a moderating factor. The research sample consists of mining and property companies listed on the Indonesia Stock Exchange during the period 2019-2022, selected using purposive sampling method. This study utilizes panel data regression and employs Eviews version 12 as the analytical tool. The research findings indicate that tax avoidance does not have a significant influence on corporate risk. However, tax risk has a positive and significant effect on corporate risk. The variable of institu-tional ownership does not affect the relationship between tax avoidance and corporate risk, but it does influence the relationship between tax risk and corporate risk. Additionally, the variable of independent commissioners does not have an impact on the relationship between tax avoidance and tax risk on corporate risk